Megaloblastic anemia with peripheral neuropathy, a misleading initial presentation in POEMS syndrome: A case report - Iadarilang Tiewsoh; Vineeta Singh; U N Jajoo (Wolters Kluwer Medknow Publications, 2014)
POEMS (peripheral neuropathy, organomegaly, endocrinopathy, M protein, skin changes) syndrome is a rare multisystem paraneoplastic disorder that occurs in the setting of a plasma cell dyscrasia. A 57-year-old male with initial presentation of peripheral neuropathy of lower limbs and a peripheral blood picture of megaloblastic anemia, presented with progressive lower motor neuron weakness over few months; followed by additional features of skin hyperpigmentation, generalized lymphadenopathy, erectile dysfunction, weight loss, and an attack of cerebrovascular accident (stroke infarct) which recovered. On further evaluation with time, there were presence of hepatosplenomegaly, Castleman's disease of the lymph node on biopsy, serum electrophoresis suggestive of monoclonal gammopathy with light band lambda chain, and endocrinopathy (hypothyroidism and hypogonadism). His bone marrow was suggestive of plasmacytosis. This case report describes a patient who presented with initial picture of peripheral neuropathy with megaloblastic anemia, but when followed-up there were diverse clinical manifestations fulfilling the diagnostic clinical criteria of POEMS Syndrome.